(untitled) (The Pakistan Development Review, 2002)
The various form of inflow of foreign capital (loans, FDI, grant and portfolio) was welcome in developing countries to bridge the gap between domestic saving and domestic investment and therefore, to accelerate growth [Chenery and Strout (1966)]. Some other have been challenged the traditional view that foreign aid impedes domestic savings growth and mobilisation and have economic growth.1 Much attention have been paid in past 30 years, relationship between foreign capital flows and domestic saving, the main purpose of these studies have been determined whether in less developed countries foreign capital inflow and domestic saving are complementary or substitute. However, there is a controversy at theoretical and empirical levels, over the effects of foreign capital on both economic growth and national saving. A number of studies in Pakistan have been conducted during the early 1990s to examine the relationship between saving and foreign capital inflow.2 All studies shows the inverse relationship between foreign capital inflows3 (aggregate level) and saving rate, but the impact of FCI at disaggregate levels (loans, grants, FDI) on saving rate show different magnitude and signs, similarly impact of FCI on decomposition of saving rate (Public, private, household, corporate) also have different magnitude and sign.